Rectenna Designs For RF Energy Harvesting System : A Review - Qasem Ahmed, Sharif Ahmed; Husain, Mohd Nor; Zakaria, Zahriladha; Mohd Zin, Mohd Shahril Izuan; Alhegazi, Ammar (Prise Worthly Prize, 2016)
-